The analysis of prognostic factors in adenocarcinoma of the cardia following surgical treatment - Mielko, Jerzy; Polkowski, Wojciech; Skomra, Danuta; Dąbrowski, Andrzej; Szumiło, Justyna; Korobowicz, Elżbieta; Wallner, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2005)
The aim of the study is an analysis of survival for patients with adenocarcinoma of the cardia with respect to tumour (biology) – and surgeon-related factors. Material and methods: Between 1998 and 2000, total gastrectomy with resection of the lower oesophagus was done in 59 patients for type II carcinoma of the gastric cardia according to Siewert classification. Survival analysis was performed in 53 patients, in whom the follow-up data were complete. Age of the patients ranged from 26 to 76 years (mean ±SD: 56.6±10.6), male: female ratio: 3.4: 1. The following factors were analysed: age and gender of patients; stage, grade (G), and histological type of the tumours according to Laurén classification, surgical approach, radicality of resection, range of lymph node dissection, lymph node index. Results: The follow-up time ranged from 3 to 107 months (mean ±SD: 28.5 ±26.3). The overall 3- and 5-year survival rates were 33% and 17%, respectively. In the univariate analysis, stage (ac. UICC 1997), pT category, radicality of resection and lymph node index influenced 5-year survival. In the multivariate analysis, only local spread of the tumour (pT category) was an independent prognostic factor (p=0.02; Cox regression model). Radicality of resection was an independent prognostic factor in the subgroup of patients with pT2 and pT3 tumour (p = 0.036; long-rank test). Conclusions: Stage of the tumour is the only significant and independent prognostic factor in patients with carcinoma of the cardia undergoing resection. Radicality of resection is a significant prognosticator in patients with tumours of limited advancement (<pT3 and <pN2).